Preparation and characterization of mixed SnO2:CdO thin films as gas sensor - Suhail, Mahdi Hasan (Iraqi Journal of Physics, 2019)
In this study, tin oxide (SnO2) and mixed with cadmium oxide (CdO) with concentration ratio of (5, 10, 15, 20)% films were deposited by spray pyrolysis technique onto glass substrates at 300ºC temperature. The structure of the SnO2:CdO mixed films have polycrystalline structure with (110) and (101) preferential orientations. Atomic force microscopy (AFM) show the films are displayed granular structure. It was found that the grain size increases with increasing of mixed concentration ratio. The transmittance in visible and NIR region was estimated for SnO2:CdO mixed films. Direct optical band gap was estimated for SnO2 and SnO2 mixed CdO and show a decrease in the energy gap with increasing mixing ratio. From Hall measurement, it was found that all the films prepared possess n-type carriers of the charge. The maximum sensitivity of SnO2:CdO mixed films toward NO2 gas was achieved at (10) mixed concentration ratio of CdO at the optimal operating temperature 200°C and maximum sensitivity is equal to (101.75%) with response time (14.6 s) and recovery time (57.0 s).